"It's really addictive and I'm trapped:" A qualitative analysis of the reasons for quitting vaping among treatment-seeking young people. (January 2021) - Amato, Michael S.; Bottcher, Mia M.; Cha, Sarah; Jacobs, Megan A.; Pearson, Jennifer L.; Graham, Amanda L.
Highlights: Many young e-cigarette users want to quit; little research has examined reasons why. We coded reasons provided by a sample of 2, 000 young treatment-seekers in 2019. Half (50.9%) reported quitting for health reasons. Money, freedom from addiction, social influence, and performance were also common. Quotes illustrate diverse negative life impacts to school, family, and social life. Abstract: Background: Debate continues over how e-cigarettes have impacted the health of young people, and what regulatory policies should be enacted. The debate has appropriately been informed by quantitative studies, often focused on initiation, prevalence, and product transition among the general population and demographic segments. Factors driving cessation and subjective experiences that motivate young users to quit have been largely absent from the debate. This qualitative study highlights the range of motivating experiences among a population of treatment-seeking young e-cigarette users. Methods: Three researchers coded reasons for quitting provided by a sample of n = 1000 youth (13–17) and n = 1000 young adults (18–24) enrolled in a text message cessation program. Data spanned January 18 – February 22, 2019. Codes were adapted from previous literature. Results: The most common reasons were health (50.9%; "I want my lungs back"), financial cost (21.7%; "I don't have enough money to feed my addiction"), freedom from addiction (16.0%; "i hate juuling. it's taking over my life"), and social influence (10.1%; "it's affecting my friendships"). Selected quotes highlight a broad range of additional ways in which e-cigarette use negatively impacted young people, including decreased academic performance and mental health. Conclusions: Young people trying to quit e-cigarettes are motivated by a diversity of reasons including health, financial, social, and academic. The range of impacts should be considered in discussions of policies intended to protect young people, and incorporated into cessation programs designed to serve them.